2020
DOI: 10.1159/000510661
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy and Hepatic Steatosis: Impact on Postoperative Morbidity and Survival after Liver Resection for Colorectal Liver Metastases

Abstract: <b><i>Background:</i></b> Hepatic steatosis and chemotherapy in the treatment of colorectal liver metastases (CLM) are often linked to increased mortality and morbidity after liver resection. This study evaluates the influence of macrovesicular hepatic steatosis and chemotherapeutic regimes on graded morbidity and mortality after liver resection for CLM. <b><i>Methods:</i></b> A total of 323 cases of liver resection for CLM were retrospectively analysed using uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The proportion of male patients ranged from 32.2 to 70.1%. Three studies ( 20 22 ) did not report data on the use of neoadjuvant chemotherapy. Only one study ( 15 ) reported data on body mass index (BMI) in the study and control groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of male patients ranged from 32.2 to 70.1%. Three studies ( 20 22 ) did not report data on the use of neoadjuvant chemotherapy. Only one study ( 15 ) reported data on body mass index (BMI) in the study and control groups.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies selected for full-text analysis, seven studies were excluded with reasons. A total of nine studies fulfilled the eligibility criteria and were included in this review (12)(13)(14)(15)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations